PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS EKONOMI KREATIFOLEH DINAS PERDAGANGAN PERINDUSTRIAN, KOPERASI USAHA KECIL DAN MENENGAH (Studi Kasus Pada Oleh-Oleh Sijunjung Kalamai Urang Awak) - Yenni Jufri; Yurismen Efendi; Ade Satya Pratama (Jurnal Public Administration, Business and Rural Development Planning, 2021)
The research objectives are: 1) To find out how the development of MSMEs based on creative economy by the Department of Trade, Industry, Small and Medium Enterprises Cooperatives in Sijunjung Regency. (Case Study On Souvenirs Sijunjung Kalamai Urang Awak). 2) To find out what factors influence the development of MSMEs based on creative economy by the Department of Trade, Industry, Small and Medium Enterprises Cooperatives of Sijunjung Regency. (Case Study On Souvenirs Sijunjung Kalamai Urang Awak). This study uses a descriptive method, where the researcher tries to describe all phenomena, symptoms, events according to the research problem as it is. Based on the descriptions in the previous chapters, the authors draw the following conclusions: 1) Development of Micro, Small and Medium Enterprises (MSMEs) based on creative economy by the Department of Trade, Industry, Small and Medium Enterprises Cooperatives of Sijunjung Regency. (Case Study On By By Sijunjung Kalamai Urang Awak) are as follows; a) Increasing market access and increasing market share, the Kalamai urang crew distributes their products to various distributor areas, even to Palembang and Jambi. b) Increasing access to capital sources and strengthening the capital structure, the business capital of Kalamai Urang crew came from one owner and no outside help. c) Improving organizational and management capabilities, They sent its members to attend trainings held by the Department of Trade, Industry, Small and Medium Enterprise Cooperatives of Sijunjung Regency such as product marketing, product pachaging training, product quality training, and product development training. d) Increasing access and mastery of technology, that the marketing technology used by SMEs is kalamai urang crew with social media such as Instagram and Facebokk. Technology for the production of MSMEs still does not use sophisticated technology.2) Factors influencing the development of Micro, Small and Medium Enterprises (MSMEs) based on creative economy by the Department of Trade, Industry, Small and Medium Enterprises Cooperatives of Sijunjung Regency. (Case Study on Souvenirs of Sijunjung Kalamai Urang Awak) including: Capital, Experience with creativity, Operations